Preparation and Evaluation of Fenticonazole Nitrate Loaded Topical Emulgel for the Treatment of Cutaneous Candidiasis: Research Article (Journal of Pharma Insights and Research, 2024)
Fenticonazole nitrate is a broad-spectrum antifungal agent possessing fungicidal, antiparasitic, and fungistatic activities. It is effective against various fungi, including Candida species, dermatophytes, and Trichomonas, which are associated with skin and vaginal infections. Emulgel systems have gained significant attention as topical drug delivery vehicles due to their ability to incorporate a wide range of therapeutic molecules, including both hydrophobic and hydrophilic drugs. The primary objective of this study was to develop an emulgel formulation of fenticonazole nitrate for the treatment of cutaneous candidiasis (cutaneous moniliasis). Conventional emulsions often face stability issues during manufacturing and storage, which can impact drug release patterns. To overcome these challenges, the emulsion was incorporated into a gel base to enhance stability. Emulgels offer significant advantages over traditional and newer vesicular systems, such as improved therapeutic efficacy, higher drug entrapment capacity, better physiological and biological compatibility, and enhanced stability. In this study, the primary oil-in-water (o/w) emulsion was prepared using a surfactant and co-surfactant mixture (3:1 ratio) incorporated with light liquid paraffin. After characterization and optimization, the final emulsion batch was mixed with the gelling agent HPMC K4M (1:1 ratio) to obtain the emulgel formulation. The optimized emulgel exhibited optimal drug release and satisfactory results in various evaluation parameters, making it a promising topical delivery system for fenticonazole nitrate in the treatment of cutaneous candidiasis